PENGARUH LAYANAN KONSELING KELOMPOK CBT DENGAN TEKNIK RESTRUKTURISASI KOGNITIF TERHADAP KETERAMPILAN SOSIAL SISWA TERISOLIR - Muawiyah; Rita Sinthia; MT Afriwilda (UNIVERSITAS BENGKULU, 2025)
Abstract This research aimed to determine the effect of CBT group counseling services with cognitive restructuring techniques on the skills of isolated students. This research method used a Nonequivalent Control Group Design experiment. The population in the study was eighth-grade students of SMP Negeri 11 Kota Bengkulu. The research sample consisted of 12 students selected using a purposive sampling technique based on the results of social skills questionnaires and sociometric questionnaires. The research was conducted by comparing two groups that were given different services, where the experimental group was more effective than the control group. The t-test result for the experimental group and the control group was 3.095. This indicated that the results of this study showed an effect of CBT group counseling services with cognitive restructuring techniques on improving the social skills of isolated students. Keywords: social skill, CBT group counseling, restructuring cognitive